ENGLISH- HISTORICAL ANALYSIS OF MADRASAS IN PAKISTAN - Jalil Ahmed; Asad Raza Talpur (دی اسکالر)
The history of madrasas is as old as back to the 11th Century. The prime aim to establish the madrasas was to educate the people, especially the Muslims, and transfer their religious understanding. During Muslim rule, the madrasas got popular, and later in the British era the growth of madrasas was there and the madrasas also played a vital role in independence later after the creation of Pakistan the madrasas played an important role. The paper will examine the history of madrassa in Pakistan.